A Case of Granulomatous Interstitial Nephritis Associated with Mycobacterium chimaera Disseminated Infection - Martina Cacciapuoti; Maria Mazzitelli; Elena Naso; Maria Loreta De Giorgi; Giovanni Samassa; Valentina Di Vico; Serena Marinello; Lucia Federica Stefanelli; Lorenzo Calò; Annamaria Cattelan; Federico Nalesso (Microorganisms)
Mycobacterium chimaera infections are becoming increasingly frequent in patients with a history of cardiac surgery. We herein report a case of a patient admitted to the Nephrology Unit of Padua University Hospital with deteriorating kidney function, pancytopenia, hypercalcemia, and respiratory symptoms that emerged seven years after they underwent heart surgery for prosthetic aortic valve replacement. A kidney biopsy revealed non-caseating necrotizing granulomatous interstitial nephritis, which was initially diagnosed as idiopathic granulomatous interstitial nephritis. The patient was treated with intravenous corticosteroids since no active infections, including mycobacterial infections, were detected. The negativity of the Mycobacterium molecular test following the kidney biopsy delayed the diagnosis of a Mycobacterium chimaera disseminated infection with endocarditis, myositis, cerebral, and kidney involvement, as blood cultures were available only after six weeks. The patient was started on antimicrobial therapy with azithromycin, moxifloxacin, rifampicin, and ethambutol while prednisone was tapered down, leading to an improvement in kidney function, blood count, and blood calcium level. Our case suggests that a Mycobacterium chimaera infection should be considered for patients with a history of cardiac surgery and granulomatous interstitial nephritis even in the absence of mycobacteria in a kidney biopsy.